2019
DOI: 10.1038/s41699-018-0085-z
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependent electronic properties of Pt dichalcogenides

Abstract: Platinum-based transition metal dichalcogenides have been gaining renewed interest because of the development of a new method to synthesize thin film structures. Here, using first-principles calculation, we explore the electronic properties of PtX 2 (X = S, Se, and Te) with respect to film thickness. For bulk and layered structures (1 to 10 layers), octahedral 1T is the most stable. Surprisingly, we also find that the 3R structure has comparable stability relative to the 1T, implying possible synthesis of 3R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
158
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(180 citation statements)
references
References 64 publications
20
158
2
Order By: Relevance
“…Such interaction produces large distortions of the valence band, which now presents two clear quasi-degenerate VBM near Γ along the Γ-M and Γ-K directions. In fact a closer inspection reveals that the VBM is formed by a set of kpoints arranged arranged along a hexagon at the edge of the 2D Brillouin zone, a fact already observed before [30].…”
Section: A Bandstructuresupporting
confidence: 57%
“…Such interaction produces large distortions of the valence band, which now presents two clear quasi-degenerate VBM near Γ along the Γ-M and Γ-K directions. In fact a closer inspection reveals that the VBM is formed by a set of kpoints arranged arranged along a hexagon at the edge of the 2D Brillouin zone, a fact already observed before [30].…”
Section: A Bandstructuresupporting
confidence: 57%
“…The bands with the flat features in 1T PdTe 2 ( figure 6(d)), however, is positioned relatively below the Fermi level. Nevertheless, the location of the flat band can be manipulated through strain [21] to tune the vHs for monolayer 1T PdTe 2 . Focusing on PdS 2 and PdSe 2 , the flat peaks bands observed are within the VBM.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also demonstrated that the electronic properties of TMDs can easily be engineered and manipulated by tuning its thickness [21][22][23] or introduction of strain [21,[24][25][26][27], in which some of the observed phenomena were increasing and indirect-to-direct transition of band gap from bulk to monolayer, and tuning of van Hove singularity (vHs) [28] near the Fermi level. Because of these unique properties, TMDs are now one of the fascinating prospects in condensed matter research, especially in 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 One member of the NTMD group is platinum disulde (PtS 2 ), of which ultrathin lms have recently been synthesised. [22][23][24] Theoretical and experimental studies have revealed that the size of the bandgap in PtS 2 decreases with increasing lm thickness, [23][24][25][26] going from $1.7 eV for monolayer PtS 2 to $0.25 eV for the bulk state. Indirect bandgaps were observed for all layer thicknesses as opposed to MoS 2 and WS 2 where the monolayer forms possess a direct bandgap.…”
Section: Introductionmentioning
confidence: 99%